Contributions of nursing care to pregnant women with anxiety: prevalence and associated factors (Research, Society and Development, 2021)
Analyze the published scientific evidence about the contributions of nursing care to pregnant women with anxiety: prevalence and associated factors. The present study deals with a bibliographic review of the integrative literature review method, carried out in the months between January and April 2021. The search was carried out, through the - VHL Platform, using the databases LILACS, BDENF, Google Scholar and through the Electronic Health Library - SCIELO. Adhering to the descriptors / keywords: “Nursing care”, “Anxiety”, “Gestation”, combined with the Boolean operator “AND”. Pregnancy involves changes in hormonal, physical, psychological, family and social aspects, in the possibility of adjustments and restructuring in women's lives. These changes have often triggered a process of vulnerability to pregnant women, which can worsen mental health and develop mental disorders. The prevalence of anxiety afflicts about 20% of women. Thus, the obstetric risks that involve the development of a pregnancy put the woman in a state susceptible to anxiety, leaving her dual: fragile, for fear of pregnancy changes, and at the same time happy for the process of conceiving and forming a new life . It was evidenced in the study, that it is necessary that nurses perform a full reception during the prenatal period, investigating clinical and also psychosocial issues so that they can contribute, in a significant way, in the improvement of the levels of anxiety and depression of this pregnant woman, providing quality prenatal care.